'The Wheel is Crooked': Hannah Arendt, action, public happiness, success, and the role for other emotions in political action - Cain, Alex (HannahArendt.net, 2024)
In this article I show that Hannah Arendt sought to rescue action and public happiness from utilitarian notions of success, such that we can understand why human beings engage in political action even when the likelihood of successfully achieving a political aim is low. First, I elucidate Arendt’s claims in a little discussed essay titled “Action and the ‘Pursuit of Happiness’” in which Arendt tells the story of “an inveterate gambler”. In the story, the gambler arrives late in a town, asks to be taken to the only gambling wheel in town, and is eager to play even though he is told that the wheel is crooked. Arendt explains that the story, “tells us that there exists such intense happiness in acting that the actor, like the gambler, will accept that all the odds are stacked against him.” Second, I show that for Arendt, this story shows that public happiness is not dependent on success. At the end of Thinking, the first volume of The Life of the Mind, Arendt turns to the following phrase, attributed to Cato the Elder: “The victorious cause pleased the gods, but the defeated one pleases Cato.” Cato was a soldier, a politician, and an historian. He was also—it goes almost without saying—human, that is, not a god. I show that the defeated cause pleases the historian and human being precisely because it is incomplete, imperfect, and thus human. Meanwhile, the complete, successful cause, with a clear beginning, middle, and end, pleases the gods. It is only in the defeated cause that the joy of speaking and acting together shows itself for what it is, since it is separated from the joy of success. Third, I temper Arendt’s account of public happiness, by arguing that her observations regarding public happiness do not preclude the need for other emotions to be involved in motivating human beings to engage in political action. Political action is not simply the joyful coming together of human beings in protest or conversation, but must have a content, must have a specific aim participants wish to achieve, which will often be a response to injustice. To make this claim I turn to Myisha Cherry’s work on anger, and more specifically on what she calls Lordean rage. In the aftermath of the Black Lives Matter protests, Cherry argues convincingly that there is a role for rage in political struggle and discourse. Lordean rage is a response to a specific form of injustice: racism. Cherry argues for a role for Lordean rage precisely because it can motivate political action, and she offers several practical ways in which both people of colour and allies can harness rage positively and productively. In this article I conclude that public happiness and Lordean rage, as well as other emotions in other contexts, can coexist, and that protestors can be both motivated by emotions such as Lordean rage and feel a sense of joy at acting together.